Integrating social concerns into electricity planning - Ferreira, Paula Varandas (2008)
This paper deals with the complexity of the social issues surrounding electricity planning. A methodology is presented establishing a possible way of allocating weights to the most important social impacts of the electricity generation options and extending these results to the evaluation of future electricity plans. The process combined Delphi method with the Analytic Hierarchy Process, for the pairwise comparison of the electricity generation technologies against the social criteria. A social impact score was then derived and assigned to each technology. In order to obtain a final ranking of future feasible plans, these overall social scores of the electricity generation alternatives were aggregated using an additive function. The final output of the social analysis is an Average Social Index of each possible electricity generation mix.